DAMPAK KEBERADAAN SARANG RAYAP TERHADAP SIKLUS NITROGEN PADA LAHAN GAMBUT TERDEGRADASI DI DESA TANJUNG LEBAN KABUPATEN BENGKALIS - Fransisca '; Tengku Ariful Amri; Sofia Anita (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Peat soil in the Bengkalis Regency, Riau Province, degrades partially due to fires and land clearing so that decreases soils fertility. Therefore, a solution is needed to increase the fertility of peatlands. This study aimed to understand the effect of termite nest presence on nitrogen cycle at the degraded peatlandecosystem in the Tanjung Leban Village, Bengkalis Regency. The measured parameterswere the amount of ammonium (NH4+) and nitrate (NO3-) ions in soil samples around termite nests, and they were analyzed using an Auto-analyzer. The analysis results of 10 termite nests indicated that the highest values of NH4 + and NO3-ions were in soil samples S8and S 10, respectively. In addition, the other soil samples and control didnot show a significant difference. Based on this results, we concluded that the termite nests in the study sites generally did not significantly affect the nitrogen cycle in thatarea. This results were based on the analysis of variance (ANOVA) and Duncan's test at α=0.05.